Urmylation: A Ubiquitin-like Pathway that Functions during Invasive Growth and Budding in Yeast - Goehring, April S. (The American Society for Cell Biology, 2003)
Ubiquitin is a small modifier protein that is conjugated to substrates to target them for degradation. Recently, a surprising number of ubiquitin-like proteins have been identified that also can be attached to proteins. Herein, we identify two molecular functions for the posttranslational protein modifier from Saccharomyces cerevisiae, Urm1p. Simultaneous loss of Urm1p and Cla4p, a p21-activated kinase that functions in budding, is lethal. This result suggests a role for the urmylation pathway in budding. Furthermore, loss of the urmylation pathway causes defects in invasive growth and confers sensitivity to rapamycin. Our results indicate that the sensitivity to rapamycin is due to a genetic interaction with the TOR pathway, which is important for regulation of cell growth in response to nutrients. We have found that Urm1p can be attached to a number of proteins. Loss of five genes that are also essential in a cla4Δ strain, NCS2, NCS6, ELP2, ELP6, and URE2, affect the level of at least one Urm1p conjugate. Moreover, these five genes have a role in invasive growth and display genetic interactions with the TOR pathway. In summary, our results suggest the urmylation pathway is involved in nutrient sensing and budding.